Safety verification method for preventing friction blisters during utilization of physical assistant robots. (3rd July 2017) - Mao, Xuewei; Yamada, Yoji; Akiyama, Yasuhiro; Okamoto, Shogo; Yoshida, Kengo
Graphical Abstract: Abstract: This study is mainly concerned with the potential hazards of interactive friction force on a human–robot contact surface, which may result in various skin traumas, such as friction blisters. In this study, a novel safety verification method is developed for helping physical assistant robot users to avoid this hazardous condition. First, based on the microscopic structure of the epidermis–dermis layer and the characteristics of blisters on porcine skin, we prove that the porcine skin, instead of the human skin, is feasible as an innovative experimental material for generating friction blisters. Second, the conditions for generating blisters on porcine skin are confirmed using a series of adaptive time-gradient tests. Considering the properties of the censored results, we clarify an inherently safe region in the tangential traction–time relationship, which is based on a nonparametric estimation of the survival function on the subjects. After a condition-matching calculation, this region for the porcine skin is further verified to be consistent with that for the human skin. Third, the safety of the 'stand-up and sit-down' motion of a physical assistant robot user is successfully validated by applying this verification method, which finally proves its practical usability with regard to the possible physical stress hazard.